1998
DOI: 10.1021/js970316d
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Metabolism of Bisoprolol Enantiomers in Humans

Abstract: The plasma concentrations and urinary excretions of bisoprolol enantiomers in four Japanese male healthy volunteers after a single oral administration of 20 mg of racemic bisoprolol were evaluated. The AUC(infinity) and elimination half-life of (S)-(-)-bisoprolol were slightly larger than those of (R)-(+)-bisoprolol in all subjects. The metabolic clearance of (R)-(+)-bisoprolol was significantly (P < 0.05) larger than that of (S)-(-)-bisoprolol (S/R ratio: 0.79+/-0.03), although the difference was small. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 21 publications
1
30
1
5
Order By: Relevance
“…3) Moreover, they suggested that CYP2D6 has a minor role but CYP3A4 plays a major part in the metabolism of bisoprolol, because the content of CYP2D6 in the human liver is much lower than that of CYP3A4. 3,20) The present findings that the non-renal clearance was not altered by the CYP2D6 and CYP2C19 genotypes may be consistent with the report of Horikiri et al 3,20) On the other hand, more than 30 single nucleotide polymorphisms have been identified in the CYP3A4 gene. 21) For the most common variant CYP3A4*1B, increased transcription was demonstrated in vitro, which may theoretically result in higher enzymatic activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) Moreover, they suggested that CYP2D6 has a minor role but CYP3A4 plays a major part in the metabolism of bisoprolol, because the content of CYP2D6 in the human liver is much lower than that of CYP3A4. 3,20) The present findings that the non-renal clearance was not altered by the CYP2D6 and CYP2C19 genotypes may be consistent with the report of Horikiri et al 3,20) On the other hand, more than 30 single nucleotide polymorphisms have been identified in the CYP3A4 gene. 21) For the most common variant CYP3A4*1B, increased transcription was demonstrated in vitro, which may theoretically result in higher enzymatic activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] In elderly patients, however, the age-associated decline in glomerular filtration and renal tubular secretion can affect the elimination of a drug dependent on the kidney for excretion. 6) In addition, hepatic drug metabolism may be diminished due to decreases in hepatic blood flow, liver mass, and levels of cytochrome P450 (CYP) drug-metabolizing enzymes.…”
mentioning
confidence: 99%
“…It is apparent that most of the commonly used β-blockers are either metabolized by CYP2D6 or eliminated by renal excretion 3,[12][13][14][15][16][17][18][19] ; thus, an awareness of which commonly used antidepressants significantly inhibit CYP2D6 10,11,[20][21][22][23][24][25] will warn clinicians about the risk of a potential drug interaction. Table 3 also lists antidepressants that are mild inhibitors of CYP2D6 10,23,25,26,[29][30][31] ; these are probably associated with lower risk of CYP2D6 drug interactions at usual clinical doses.…”
Section: Other Antidepressants and Other β-Blockersmentioning
confidence: 99%
“…Il est sélectif de ces récepteurs cardiaques [4][5][6], limitant ainsi son tropisme vasculaire. Cette molécule a une action anti-ischémique et anti-arythmique.…”
Section: Rappels Pharmacologiquesunclassified